BLACK COMPANY AS SOCIAL PROBLEM IN JAPANESE FILM: A SOCIO-LITERARY AND READER RESPONSE ANALYSIS - Mulyadi, S.Pd.,M.Hum., Budi; Rahwati, Wawat; Angela, Bella (Vocational College of Diponegoro University, 2024)
This study examines the issue of black companies (buraku geisha) in two Japanese films: Burakku Gaisha ni Tsutometerundaga, Mou Ore wa Genkai Kamoshirenai (2009), and Chotto Ima Kara Shigoto wo Yamete Kuru (2017). Black companies are a social problem in Japanese society, where many companies exploit their employees by forcing them to work excessive hours for low wages. This has become a serious issue, leading to the phenomenon of karoshi, or death because of overwork. The research analyzes how the two films portray the black company issue and the perspectives of the characters in these films towards it. This research also examines how Japanese society responds to the problem as depicted in the films. This qualitative research employs a combined approach of sociological literary and reader-response perspectives, focusing on the societal aspects of the film by examining the discourses related to social problems and the social itself. The result based on that analysis of the films and the application of the two perspectives shows that the characters’ views provide a reflective portrayal of the social issues currently faced by Japanese society